Doublecortin immunolabeling in canine gliomas with distinct degrees of tumor infiltration. (March 2023) - Reyes, Vicente A. A.; Donovan, Taryn A.; Miller, Andrew D.; Porter, Brian F.; Frank, Chad B.; Rissi, Daniel R.
Increased doublecortin (DCX) immunolabeling at the tumor margins has been associated with tumor infiltration in human glioma and canine anaplastic meningioma. No association between DCX immunolabeling and glioma infiltration has been reported in dogs, to our knowledge. Here we compare the DCX immunolabeling in 14 diffusely infiltrating gliomas (gliomatosis cerebri) and 14 nodular gliomas with distinct degrees of tumor infiltration. Cytoplasmic DCX immunolabeling was classified according to intensity (weak, moderate, strong), distribution (1 = <30% immunolabeling, 2 = 30–70% immunolabeling, 3 = >70% immunolabeling), and location within the neoplasm (random or at tumor margins). Immunolabeling was detected in 6 of 14 (43%) diffusely infiltrating gliomas and 8 of 14 (57%) nodular gliomas. Diffusely infiltrating gliomas had moderate and random immunolabeling, with distribution scores of 1 (4 cases) or 2 (2 cases). Nodular gliomas had strong (6 cases) or moderate (2 cases) immunolabeling, with distribution scores of 1 (3 cases), 2 (3 cases), and 3 (2 cases), and random (6 cases) and/or marginal (3 cases) immunolabeling. Increased DCX immunolabeling within neoplastic cells palisading around necrosis occurred in 4 nodular gliomas. DCX immunolabeling was not increased at the margins of diffusely infiltrating gliomas, indicating that DCX should not be used as an immunomarker for glioma infiltration in dogs.